Conflict Between Direct Experience and Research-Based Evidence Is a Key Challenge to Evidence-Based Respiratory Medicine on British Racing Yards - Kinnison, Tierney; Cardwell, Jacqueline M. (Frontiers in Veterinary Science, 2020)
Inflammatory airway disease (IAD) is a commonly diagnosed but variably defined syndrome of equine lower airway inflammation. The most recent American College of Veterinary Internal Medicine (ACVIM) consensus statement, informed by research evidence, recommends a case definition based on clinical signs (poor performance or occasional coughing of at least 3 weeks duration), increased endoscopically-visible tracheal mucus, and bronchoalveolar lavage cytology, and proposes that the condition should be termed ‘mild-moderate equine asthma’ (mEA). In British Thoroughbred racehorses, research to date has focused on airway inflammation defined by increased tracheal mucus and inflammatory tracheal wash sample cytology. It has been unclear whether or to what extent the ACVIM consensus statement has influenced the practice of British racing veterinarians. The aim of this qualitative study was to characterise and understand rationales for current practices relating to diagnosing and managing airway inflammation in British racehorses. Audio-recorded focus group discussions were conducted with 25 participants from four veterinary practices in England. Practices were purposively selected to represent those responsible for different types of racehorse, in different geographical regions. Thematic analysis of transcripts identified (i) an over-arching theme of serving the racing industry within which two further themes (ii) disregarding of the consensus and (iii) the pragmatic clinician were nested. The requirement to serve the racing industry was a key driver of clinical approaches, strongly influenced in particular by the trainer. Participants widely disregarded the consensus case definition of IAD/mEA for British racehorses because of perceived differences in aetiology, perceived lack of practicability, particularly of BAL sampling, and perceived lack of understanding of the British racing context by consensus authors. Participants shared a strong professional identity as pragmatic clinicians providing an individualised clinical approach based on direct experience, which was often prioritised as the most valuable evidence with which to inform clinical decision-making. Lack of alignment with international consensus presents a barrier to practising and furthering evidence-based medicine. Improved dialogue and partnership in research would be valuable and further research tailored for this population, including continuing development of contextually acceptable diagnostic methods, may be required.